Does Corruption Have a Bad Impact on Local Government Performance - Khairudin Khairudin; Rahmawati Rahmawati; Jaka Winarna; Evi Gantyowati (Ilomata International Journal of Social Science, 2023)
Good government performance can increase organizational value, legitimacy, public support and also increase organizational survival. However, the performance of local governments based on HDI is still not good and places Indonesia below ASEAN countries such as: Singapore, Brunei Darussalam, Malaysia and Thailand. This study aims to examine the effect of corruption on local government performance, where this research was conducted on 34 provincial governments in Indonesia during the 2016-2020 period. This research is interesting because it has novelty in terms of measuring local government performance and corruption. Local government performance is measured using the Human Development Index whose data comes from BPS-RI and corruption is measured by the value of the rupiah audit findings by BPK-RI on budget implementation and efforts to fight corruption. The test results using panel data regression with the fixed effect model show that corruption has a positive and significant influence on local government performance.